Effect of rubella vaccine to plasmodium-infected mice parasitemia levels - Jonny K. Fajar; H. Harapan; Kurnia F. Jamil; Tjut M. Zanaria (Syiah Kuala University, 2012)
Malaria, an infectious disease causes by Plasmodium, contribute to 300-900 million morbidities and 1-3 million mortalities, annually. This study aimed to determine the Rubella vaccine potency to inhibit Plasmodium berghei merozoite invasion to erythrocyte which evaluated from parasitemia levels, mortality and mice clinical condition. This study conducted in mice injected Rubella vaccine prior injected with P. berghei. There were four groups: A, B and C injected with 500 µl, 2 µl, and 1 µl rubella vaccine respectively. Group D injected with 500 µl sterile aqua, as control group. After 28 days of vaccination all mice injected with 0.2 ml P. berghei. Furthermore, we observed to parasitemia levels, death, and clinical condition of mice to assess Rubella vaccine effectiveness to inhibit merozoite invasion. The results shown Rubella vaccine did not provide significant effect on parasitemia levels. It might Rubella vaccine dose we used under effective dose and less effective of target site. However, our study shown Rubella vaccine provided significant effect on mice mortality (p0.05). It is probably due to Rubella antigen (213-239 amino acid sequence) and malaria antigen merozoite surface protein (MSP)-119 (sequence amino acid 238) has similar structure, thus it was likely generated cross-immunity. In conclusion, 28 days Rubella vaccination did not provide significant effect on parasitemia levels, however it provided significant effect on mice mortality with infected by P. berghei.